A Hybrid Approach to QoS-Aware Service Composition - Xinfeng Ye; Mounla, R. (2008 IEEE International Conference on Web Services, 2008)
QoS-aware service composition intends to maximize the QoS of a composite service when selecting service providers. This paper proposes a service composition scheme that uses a combination of Integer Programming, case-based reasoning, and, genetic algorithms techniques. The scheme reduces the service composition costs by reusing existing compositions. Experiments show that, compared with solutions purely based on Integer Programming, the proposed scheme is effective in reducing the time for carrying out service composition.